Infection by haemopathogens and tick infestation of sheep during summer season in Constantine region, Northeast Algeria. Issue 5 (17th June 2021) - Foughali, Asma Amina; Jedidi, Mohamed; Dhibi, Moktar; Mhadhbi, Moez; Sassi, Limam; Berber, Ali; Bitam, Idir; Gharbi, Mohamed
Abstract: A study on tick infestation of 43 sheep with clinical symptoms of piroplasmosis and anaplasmosis was carried out during summer seasons of 2016 and 2017 in 34 sheep flocks from Beni Hamidene locality, district of Constantine, Northeast Algeria. Only animals with clinical symptoms of piroplasmosis and/or anaplasmosis were checked for tick infestation. Among the 43 examined sheep, 58 ± 15% were infested by ticks. A total of 185 adult ticks (100 males and 85 females) were collected from the 25 sheep. Two tick genera, Rhipicephalus and Hyalomma consisting of four species were collected, Rhipicephalus bursa was the most frequent tick (164/185; 88.6 ± 4.6%), followed by Rhipicephalus sanguineus sensu lato (16/185; 8.6 ± 4%), Rhipicephalus ( Boophilus ) annulatus (4/185; 2.2 ± 2.1%) and Hyalomma scupense (1/185; 0.5 ± 1%). Mean overall tick infestation intensity was 7.4. Mixed infestations with two tick species were found in 10 sheep (23.3 ± 12.6%). All farmers (34/34) used ivermectin, and only 11% of them used acaricide to control ticks. The majority of R. bursa ticks (87/185; 45 ± 7%) were located on the ears 37/185; 20 ± 6%) and the testicles (50/185; 27 ± 6%). Giemsa‐stained blood smears examination showed the presence of three haemopathogens: Anaplasma spp. (19/43; 44 ± 15%); Babesia spp. (6/43; 14 ± 10%) and Theileria spp. (1/43; 2 ± 4%). These results showed the presence of several low infestation burdens by ticks transmitting three haemopathogens. Abstract : We aimed herein to study the tick infestation during the tick season in sheep with clinical episodes or heamopathogen infections in Beni Hamidene locality, district of Constantine, Northeast Algeria.